The application of integrated multi-trophic aquaculture (IMTA) using floating net cages on Tilapia fish with native fish (Peres, Lemeduk, and Depik) - Nurfadillah Nurfadillah; Iwan Hasri; Muhammad Reza Purnama; Adrian Damora; Siska Mellisa (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2021)
Environmental problems due to aquaculture occur along with the increase in aquaculture production. IMTA is one system used as a solution in dealing with environmental problems. The objective of this study was to analyze the growth performance, survival rate, and production of the main commodity (tilapia) and the supporting commodities (Peres, Lemeduk, and Depik) which are applied through the application of integrated multi-trophic aquaculture (IMTA) using floating net cages. This research was conducted at the Lukup Badak Fish Seed Center, Central Aceh from July to August 2020. The experimental design used was a completely randomized design (CRD) with 4 treatments and 3 replications, namely: A (tilapia), B (tilapia and peres), C (tilapia and lemeduk), and D (tilapia and depik). ANOVA test results showed that the IMTA system had a significant effect on absolute length growth, absolute weight growth, specific growth rate (SGR), survival rate, and biomass production of tilapia (P0.05). The results showed that maintenance for 42 days produced the highest value in treatment B with the increase in absolute length growth (4.26cm0.24); absolute weight growth (5.47g0.45), specific daily growth rate (2.28%/day0.13) and the highest tilapia biomass production (480g/0.5m219.25). The highest survival rate was found in treatment C (82.42%2.28). It was concluded that the treatment using the IMTA system was better than without the IMTA system.Keywords:IMTAWater qualityGrowth performanceTrophic interactionBiomass production